Impact of Dysmenorrhea on Academic Performance Among Haramaya University Undergraduate Regular Students, Eastern Ethiopia - Mesele, Tiruye Tilahun; Ayalew, Hiwotie Getaneh; Syoum, Asmra Tesfahun; Antehneh, Tazeb Alemu (Frontiers in Reproductive Health, 2022)
Background: Dysmenorrhea is the most common gynecological problem among students. The disease affects students' academic performance, although studies carried out in Ethiopia primarily focused on the prevalence aspects rather than the impacts of dysmenorrhea on academic performance and its associated factors. Therefore, this study focused on the prevalence of the impact of dysmenorrhea on academic performance and its associated factors among undergraduate female students of Haramaya University in eastern Ethiopia. Methods A cross-sectional study design was conducted from February to March 2020. A multistage random sampling technique was applied and a total of 356 students were included in the study. To select students, simple random sampling was used and the sample size was proportionally allocated with respect to the total number of each selected department. A semi-structured and a pre-tested self-administered questionnaire were used. The descriptive result was presented as a proportion whereas the analytic part was presented with an adjusted odds ratio. Result The prevalence of the impact of dysmenorrhea on academic performance was 266 [(74.7%):95%CI (70.0, 79.5%)]. Premenstrual syndrome [AOR = 4.86:95%CI (2.13, 11.06)], early menarche [AOR = 4.89:95%CI (2.03, 11.77)], moderate/severe dysmenorrhea pain intensity [AOR = 8.53:95%CI (4.45, 16.39)], and students monthly pocket money <150ETB [AOR = 3.91:95%CI (1.48, 10.29)] were significantly associated with the occurrence of the impact of dysmenorrhea on academic performance. The most common impacts were difficulty in studying followed by loss of concentration in the class. Conclusion and Recommendation There was a high prevalence of impact of dysmenorrhea on academic performance among undergraduate female students of the Haramaya University. Awareness should be created among Haramaya university authorities and teachers about the academic performance impact of premenstrual syndrome and dysmenorrhea pain intensity to provide psychological and academic guidance, and managing mechanisms for the affected students. Haramaya University should also establish medical care for the affected students.